EFFECT OF SOME ENVIR0NMENTAL FACTORS ON T ACUTE TOXICITY OF DELTAMETHRIN TO COMMON CARP: A LAB0RATORY STUDY UNDER AEROBIC CONDITION - Kent, Yhunsenlo; Datta, Subhendu; Shah, Parvez Sazad; Das, Radha C. (Journal of Indian Fisheries Association, 2015)
The toxicity of xenobiotics in aquatic ecosystems is influenced by many factors such as ambient temperature, water hardness, pond soil type, etc. In the present study, it was observed that air temperature, water hardness and soil sediment have profound influence on the toxicity of deltamethrin to common carp fry (ay. length 3.5 Â± 0.5 cm, ay. weight 0.58 Â± 0.25 g); 96h LC50 values for common carp at 38.07 Â± 2.20Â° C maximum and 27.86 Â± 1.22Â°C minimum air temperature in soft and very hard water were 0.102 and 0.495 jig 1 .1 , respectively. This value had increased significantly to 2.37 and 3.02 jig Pat 30.55 Â± 1.21Â° C maximum and 26.04 Â± 0.61Â° C minimum air temperature, respectively. When sediment was included, 96h LC 50 at 38.07Â° C maximum temperature in very hard water was 1.808 lig 1’ and this had increased to 8.073 jig 1-1 when tested at 30.55Â° C maximum temperature. Due to the 7.5Â° C increase in maximum and 1.7Â° C in minimum temperature, toxicity increased significantly. Lower toxicity in very hard water in comparison to soft water may be due to the lower solubility of deltarnethrin and high level of calcium. Adsorption reaction of deltamethrin with clay, humus, FeOOH, MnOOH and particulate organic carbon, and complexation reaction with dissolved organic carbon were responsible for the lowered toxicity in the experiment with sediment. Exposure time had no significant effect on acute toxicity of deltamethrin. Keywords: Deltamethrin, common carp, temperature, water hardness, sediment